2022
DOI: 10.5770/cgj.25.536
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Healthy Aging to AVOID Frailty in Community Dwelling Older Canadians

Abstract: The Canadian population is aging. With aging, biological and social changes occur increasing the risk of developing chronic conditions and functional loss leading to frailty. Older adults living with frailty are more vulnerable to minor stressors, take longer to recover from illness, and have difficulty participating in daily activities. The Canadian Frailty Network’s (CFN) mis-sion is to improve the lives of older adults living with frailty. In September 2019, CFN launched the Activity & Exercise, Vaccina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Adoption of a multi-faceted intervention such as the ABCDEF bundle [49] during the ICU stay may be particularly relevant to frail patients and it may more effectively improve outcomes in frail patients than in non-frail patients. Further, interventions may need to be continued throughout the ward stay and after hospital discharge in the community with a focus on rehabilitation, exercise, nutrition, medication optimization and social connection [50]. Multi-disciplinary ICU follow-up clinics could be used to facilitate this.…”
Section: Discussionmentioning
confidence: 99%
“…Adoption of a multi-faceted intervention such as the ABCDEF bundle [49] during the ICU stay may be particularly relevant to frail patients and it may more effectively improve outcomes in frail patients than in non-frail patients. Further, interventions may need to be continued throughout the ward stay and after hospital discharge in the community with a focus on rehabilitation, exercise, nutrition, medication optimization and social connection [50]. Multi-disciplinary ICU follow-up clinics could be used to facilitate this.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, more public awareness campaigns such as the Canadian AVOID (Activity, Vaccinate, Optimize medications, Interact, and Diet/nutrition) campaign by the Canadian Frailty Network are urgently needed. 109 …”
Section: Therapeutic Approaches To Frailty Post‐ Covid ...mentioning
confidence: 99%
“…Implementation of nutritional intervention is particularly urgent for those who are already malnourished or have muscle impairment ( 41 , 76 , 77 ). A Canadian initiative proved effective for avoiding development of frailty ( 78 ), while results of a recent European study demonstrated that nutritional care could prevent loss of mobility ( 79 ).…”
Section: Nutrition Matters Across the Lifespanmentioning
confidence: 99%